Women's Capacity Building of Informal Sector Workers in Rural Areas (Case of "Boiled Corn Seller" In Konawe Regency, Southeast Sulawesi Province) - Yoo Eka Yana Kansil; Nana Sumarna; Rimba Hamid (Salasika, 2019)
The number of women local workers in the informal sector increases. Most of the women are those who live and work in poverty. One of the informal jobs is seller of corn on the cob, which is known as Boiled Corn Seller (BCS) women. The study is a case study with qualitative approach. These BCS women sell their corn along the provincial axis road in Pondidaha Sub-district of Konawe District, Indonesia. The data collection techniques used were observation methods, indepth interviews, and FGDs. The results showed that (1) BCS women still had access to capital resources, production facilities and labor, but faced difficulties in production equipment, labor, training and money; (2) the processing, marketing and distribution of corn on the cob were dominated by BCS women; and (3) the conceptual model planned for capacity building was a local food diversification program.